A kinematics analysis of cartwheel to straight side airspring with 630° turning in Yang Yahong's vaulting horse - Du, W.-G.; Yao, W.-G.; Wang, X.-D. (Journal of Beijing Sport University, 2008)
Through the video of vaulting horse finals in the World Gymnastics Championships from 1999-2004 and the Olympic Games,cartwheel to straight side airspring with 630°turning in Yang Yahong's vaulting horse is studied.As the first athlete who can accomplish cartwheel to straight side airspring with 630°turning,Yang Yahong has win the championship of vaulting horse for several times in national gymnastics competitions.She never fails in performing this movement with steady and high quality,and has set a good example.